The concept of zakat on livestock : understanding of students In UiTM Puncak Alam / Nuurul Syairah Nor Zan - Nor Zan, Nuurul Syairah (Academy of Contemporary Islamic Studies (ACIS), 2017)
This study was to examine the understanding of students in UiTM Puncak Alam related to zakat on livestock. The objective of this study is to determine the conditions of zakat on livestock and the conditions to be fulfilled. Moreover, it is to conduct a study on UiTM Puncak Alam students to assess their understanding of the concept of zakat on livestock and to analyse the studies that have been conducted on the student's understanding of zakat on livestock. UiTM Puncak Alam serves as the location for the study to assess their understanding of the zakat on livestock. To carry out this study, the authors used questionnaires and observation method to determine the level of understanding of the students. Data was analysed and described in the study and explanation. In conclusion, the understanding among students needs to be improved. Through this study, it is expected that the students and other people who can carry out the obligation of Zakat and expand knowledge on zakat.